Intervención del terapista respiratorio en la rehabilitación cardiopulmonar en paciente masculino de 40 años con diagnóstico de Covid-19. - Montece Medina, Yary Adriana (2022)
The present case exposes the importance of the intervention of the respiratory therapist in cardiopulmonary rehabilitation in a 40-year-old male patient diagnosed with covid-19, since his participation in the recovery process is important for the reduction of the sequelae of the disease. Respiratory therapy is part of intensive care, which is considered one of the best therapeutic options for reducing symptoms of respiratory viral infections, which includes Covid19, an affectation that has increased greatly due to its easy spread, which generates a risk of mortality or sequelae for survivors. People who have been infected require rehabilitation that physiotherapy manages to compensate, considering it a prophylactic strategy in the face of this problem. That is why the intervention by the professional must be optimal and with the necessary knowledge for the application of the techniques and thus provide care in which the patient improves their respiratory condition. Due to the fact that covid-19 is developed in stages of affectation, the required process must be carried out in each one until the patient manages to overcome the acute phase of the virus, the sequelae must be identified and assessed in order to be treated with the correct techniques.